OFFICIALLY NON-EXISTENT: STORAGE AND USE OF BANNED LITERATURE IN THE SOVIET LATVIA IN THE 1970s–1980s - Dreimane, Jana (Knygotyra, 2017)
In the Soviet Latvia (1940–1941, 1944–1990), as in other Communist-occupied countries, alongside with officially allowed media circulated alternative sources of information – forbidden and secret publications, works of cultural and intellectual movements sharply criticized or concealed by the Soviet power, etc. This paper considers storage and use of books and periodicals, published in the independent Republic of Latvia (1918–1940) and forbidden during the Soviet period. Legally this literature was accessible only at three major research libraries of the Latvian SSR to researchers and specialists with special permissions. Other professional and social groups could reach it illegally – at secret storage places of different libraries, black book markets as well as home libraries. Along with publications in the press, the archive of the central censorship body (the Main Literature Board of the Latvian SSR) and library documents, interviews with librarians and historians are used in the research.